The Challenges of Iranian Female Nurses Caring for Male Patients: A Qualitative Study - Samaneh Alinejad Mofrad; Ahmad Nasiri; Heidi Green (Wolters Kluwer Medknow Publications, 2024)
Background: Caring is a multidimensional concept with many factors that can affect its quality such as caring for the opposite sex. This study aims to explore the experiences of Iranian female nurses caring for male patients. Materials and Methods: A descriptive qualitative study was conducted via conventional content analysis and purposeful sampling. Seventeen female nurses including staff and head nurses participated. Unstructured, face-to-face, in-depth interviews were conducted from June to December 2019 in Iran. The interviews were recorded by an MP4 player. When no new codes were extracted from the interview the data saturation was achieved. All interviews were immediately transcribed verbatim and were analyzed via Graneheim and Lundman's conventional content analysis guidelines. Results: Four themes emerged from the data: 1) women nurses' concerns about caring for men, 2) women nurses' unpleasant feelings while caring for men, 3) Ignoring women nurses' dignity, and 4) efforts to avoid unpleasant situations. Conclusions: Female nurses in Iran are faced with multidimensional challenges when providing care to men. Not only can these challenges decrease the quality of nursing care for male patients, but also make the hospital a stressful environment for female nurses and may lead to them leaving the work.